2020
DOI: 10.1002/ghg.1948
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of smart carbonated water injection method in carbonates

Abstract: Enhanced oil recovery (EOR) has been noticed during recent years from reservoirs that are at the end of their life plateau or in which production has been declined. Two of these EOR methods are as follows: carbonated water and smart water injection. In carbonated water injection method, CO2‐contained water is injected in reservoirs in order to decrease free CO2 injection mobility, increase water viscosity, and store/remove produced greenhouse CO2 gas safely, and in smart water injection method, the ions in bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Soleimani et al 55 investigated the impact of CLSW on recovery under dynamic coreflooding conditions with carbonate rocks. Studies have demonstrated that lower salinity levels in CLSW result in significant improvements in wettability, thereby increasing the oil recovery.…”
Section: Alter Wettabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Soleimani et al 55 investigated the impact of CLSW on recovery under dynamic coreflooding conditions with carbonate rocks. Studies have demonstrated that lower salinity levels in CLSW result in significant improvements in wettability, thereby increasing the oil recovery.…”
Section: Alter Wettabilitymentioning
confidence: 99%
“…Moreover, at the reservoir scale, the injection capacity demonstrated a 31% improvement over CW injection. Soleiman et al prepared CW using formation water at various dilution levels, ranging from 1637 to 163711 ppm, and reached consistent conclusions. Furthermore, they found that the higher the salinity of the water, the lower the dissolved CO 2 in it.…”
Section: Enhanced Carbonated Water Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mineral precipitation has been observed experimentally at the core scale for carbonate reservoirs. 4,47 However, no study has been reported for fractured reservoirs. The heterogeneity effect on mineral dissolution appears in this system, as shown in Fig.…”
Section: Mineral Dissolution and Porosity Changesmentioning
confidence: 99%
“…Specifically, CWI offers advantages such as better microscopic sweep efficiency, increased contact time between CW and trapped oil, elimination of gravity segregation, reduction of high water saturation and water shielding effects, and facilitation of CO 2 mass transfer between trapped oil ganglia and CW. , Other favorable aspects of CWI for EOR and CGS include the reduction in required CO 2 volumes, augmented brine injectivity, wettability alteration, swelling of trapped oil globules, delayed injected phase breakthrough, and lower risk of buoyancy-driven leakage . Several recent studies have confirmed that CWI outperforms CO 2 injection and CO 2 WAG regarding EOR and CO 2 storage performance. , Ajoma et al demonstrated both experimentally and simulation-wise that water-saturated CO 2 injection stored more CO 2 (3.8 megatons) than pure CO 2 injection (2.71 megatons). Furthermore, Soleimani et al also found that hybrid smart CWI outperformed other CO 2 injection scenarios regarding oil recovery.…”
Section: Introductionmentioning
confidence: 99%